ANALISIS KESALAHAN PESERTA DIDIK BERDASARKAN TAHAPAN KASTOLAN DALAM MENYELESAIKAN SOAL MATEMATIKA KELAS XI SMAN 3 PADANG - Sinta Gabriella Sitopu (Jurnal Edukasi dan Penelitian Matematika, 2020)
The purpose of this research is to describe the errors and factors that cause students make mistakes in solving math problems based on the Kastolan stages in the linear program material. This type of research is descriptive. Subject of this research is XI MIPA 7 class of SMAN 3 Padang that six students were interviewed. The results of the research subject tended to commit a) conceptual errors as much as 49% including errors in choosing and applying the formula / concept material prerequisite for linear programming, errors in making mathematical models and the principle of maximum value of the linear program. b) procedural errors as much as 40% including errors in determining steps for completion, incomplete steps, and solutions that do not result in simple changes. c) technical errors as much as 11% of misinformation in the questions and wrong in calculating. These causes are not mastering the material with errors, after solving linear program questions, not reviewing the material, not being confident and not checking the answers. Keywords— Error analysis, Kastolan, Math problems